Analysis of The Impact of Public Budget and Economic Growth on Poverty Reduction: Empirical Study in Aceh Province - Syahril, Syahril; Irmayani, Irmayani; Nasir, M. (Teunuleh Publisher, 2025)
This study aims to analyze the impact of the Aceh Regional Budget (APBA) and Economic Growth of Aceh Province (PEPA) on the poverty rate in Aceh Province during the period 2005–2024. Using a multiple linear regression method, the findings indicate that APBA has a negative and significant effect on the poverty rate, with a coefficient of -1.69 and a p-value < 0.01. This result suggests that every 1 trillion rupiah increase in regional spending has the potential to reduce the poverty rate by 1.69%, especially when allocated to strategic sectors such as education, health, and infrastructure. In contrast, PEPA does not show a significant impact on the poverty rate (p = 0.745; coefficient = -0.086), reinforcing findings in the literature that economic growth is not always inclusive and tends to overlook poor groups if not accompanied by equitable income distribution. This study underscores the importance of well-targeted public spending in alleviating poverty and the need to shift focus from aggregate economic growth toward more inclusive and equitable development strategies.